Non-Jural Labor Practices at Kuzbass Coal Enterprises: The Experience of Sociological Analysis Within the Historical Context - Olga Urban (Journal of Economic Sociology, 2023)
Kuzbass is the largest coal mining region in Russia. Ensuring safety and labor protection is a priority area in the activities of coal enterprises and the regional government. Safety problems are significantly subjective. The accident at the Listvyazhnaya mine in November 2021 revealed safety problems in violation of regulatory requirements in everyday work. The purpose of the article is to assess the scale and causes of labor practices that violate the legal rights and obligations of the parties involved in labor relations to ensure safe work and health protection in coal mining processes. The concept of non-jural labor practices coined by T. Zaslavskaya and M. Shabanova provided a conceptual basis for the understanding of labor relations as a set of labor practices at regional coal enterprises viewed from a historical perspective. Drawing on the evidence from the scientific literature and the media, the data from sociological investigations, the state and departmental statistics, the author analyzes the non-jural labor practices at Kuzbass coal enterprises from the beginning of the restructurings in the coal industry until now. The article argues that breaking the rules and ignoring socio-cultural norms that prioritize human life and health values have been institutionalized as a set of non-jural labor practices since the early 1990s and are well established nowadays. The recommended standards of labor relations are contradicted by the everyday management and existing labor practices. It is clear that the institutionalization of non-jural labor practices is caused by the management and employees. The key factors are focused on motivating owners and management to increase coal production and profit. Improper labor practices, deteriorating the quality of human capital, create institutional obstacles to the current and future objectives of innovative development of the coal industry and the purposes of the Kuzbass–2035 regional strategy. The main directions to overcome the effects of non-jural labor practices are outlined.